Protection of Personal Data of Indonesian Migrant Workers regarding Certainty of Protection of Indonesian Migrant Workers while in the Destination Country - Muhammad Abdurrohman Sholih; Richard , Richard (PT. ALHAFI BERKAH INDONESIA, 2025)
Indonesian Migrant Workers (PMI) are a vulnerable group who face various risks in destination countries, including the potential for misuse of their personal data. As the migration process becomes digital, the volume and sensitivity of PMI data managed by various parties increases, creating a strong urgency for data protection. This study aims to analyze the relationship between personal data protection and the certainty of legal protection and overall security of PMI in destination countries. Using a qualitative research method based on secondary data analysis covering Law Number 27 of 2022 concerning Protection of Personal Data (UU PDP), Law Number 18 of 2017 concerning Protection of Indonesian Migrant Workers (UU PPMI), reports from related institutions, and case studies, this study examines the legal framework, international dimensions, risks, and implementation challenges. The findings show that the PDP Law is an important legal foundation, complementing the PPMI Law, but its implementation faces significant challenges related to institutional capacity, coordination, private sector compliance, system security, PMI literacy, and cross-border law enforcement. Strengthening comprehensive and integrated PMI data governance is urgently needed to ensure the security and certainty of protection of PMI rights abroad.